(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of correct knowledge and practices regarding rabies prevention among dog and cat owners in Mo Cay Nam district, Ben Tre province in 2025, and to identify associated factors. Subjects and methods: A descriptive cross-sectional study was conducted from March 14 to June 13, 2025, involving 399 dog and cat owners in Mo Cay Nam district, Ben Tre province. Data were collected through interviews using a structured questionnaire. Results: The study results indicate that 64.4% of the population had adequate knowledge about rabies prevention, while only 53.6% demonstrated proper preventive practices. Analysis of related factors showed that residence location and gender were significantly related to having accurate knowledge (p = 0.004). In terms of practice, gender, age group, and education level were significantly related to correct rabies prevention practices (p < 0.05). Notably, individuals with adequate knowledge about rabies prevention were significantly more likely to engage in correct preventive practices, with a very strong statistical relationship (p < 0.001). Conclusion: The study of 399 respondents revealed that correct knowledge and correct practices regarding rabies prevention among dog and cat owners remain limited and insufficient. It is necessary to implement diverse health education and communication strategies, strengthen the management, upervision and increase the rate of regular vaccination for dogs and cats.